Workforce churning, human capital disruption, and organisational performance in different technological contexts. (13th September 2017) - Della Torre, Edoardo; Zatzick, Christopher D.; Sikora, David; Solari, Luca
Abstract: We assess the influence of workforce churning on the relationship between organisational human capital and labour productivity. Building on collective turnover research and human capital theory, we examine how the components of workforce churning (i.e., voluntary turnover, involuntary turnover, and new hires) influence the relationship between existing human capital and labour productivity. Further, we examine how this influence varies according to a firm's technological intensity. Our data come from 1, 911 Italian manufacturing firms and reveals that collective voluntary turnover negatively affects the relationship between organisational human capital and labour productivity regardless of an organisation's level of technological intensity. In contrast, collective involuntary turnover enhances the relationship between human capital and labour productivity, and its effect is even stronger for organisations with more technologically intensive operations. Finally, our results suggest that the integration of new hires disrupts the relationship between human capital and productivity, particularly for firms with technologically intensive operations.